Pengaruh Kompetensi, Akuntabilitas dan Independensi Terhadap Kualitas Hasil Pengawasan oleh Inspektorat Kabupaten Sukabumi - Nurlaeliyah Rahayu; Usman Sastradipraja (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the effect of competence, accountability, and independence on the quality of supervisory outcomes conducted by the Inspectorate of Sukabumi Regency. The quality of supervisory outcomes is a crucial element in supporting the implementation of good governance, particularly in enhancing accountability and transparency in regional financial management. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to Internal Auditors and Functional Officials for the Supervision of Regional Government Affairs (P2UPD) at the Inspectorate of Sukabumi Regency. Data analysis techniques include validity and reliability testing, classical assumption tests, and multiple linear regression analysis to examine the influence of independent variables on the dependent variable. The results of this study are expected to indicate that competence, accountability, and independence have a significant effect, both partially and simultaneously, on the quality of supervisory outcomes. The findings are expected to contribute theoretically to the development of public sector accounting studies and practically to provide recommendations for improving the quality of internal supervision and strengthening accountable, transparent, and integrity-based local governance.